Global imbalances - El Kallab, Tania (2014)
Three facts have characterized the pre-crisis debates in macroeconomics: the increase in the US current account de cit, the decline in interest rates and the increase in the share of US assets in global portfolios. Caballero, Farhi and Gourinchas (2008) described these "anomalies" as being external to the United States. The high saving rates in Asian countries in the aftermath of the collapse of their nancial markets led to a high demand for American nancial assets rather than domestic Asian ones, which were now considered unsafe. Our paper uses the basic model provided by Caballero, Farhi and Gourinchas to investigate whether an alternative explanation for these three facts, namely, the increase in American consumption. We show that the increase in US consumption would indeed cause a rise in capital ows towards the US (fact 1), but interest rates would rise rather than decrease (fact 2), and the share of american assets in global portfolios would not be a ected (fact 3).